2013
DOI: 10.1002/ceat.201300368
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Liquefaction of Cypress: Effect of Water Amount on Structural Characteristics of the Solid Residue

Abstract: Hydrothermal liquefaction of cypress was performed in an autoclave with various amounts of water. The obtained acid-soluble and acid-insoluble solid residues were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, sugar analysis, elemental analysis, and nuclear magnetic resonance to help understand the reaction mechanisms of this process. The characteristics of solid residues were significantly affected by the water amount. Cellulose was more stable at high water amount and hemicellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…At a high ratio of 1/5, liquefaction was not performed well, even at a high temperature of 300 °C. Liu and Li reported that a high amount of H 2 O is suitable for HTL and many organic components in macroalgae are converted to bio-oil . It was considered that the decomposition reaction (HTL) of macroalgae in hot compressed H 2 O was clearly dependent on the H 2 O amount.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a high ratio of 1/5, liquefaction was not performed well, even at a high temperature of 300 °C. Liu and Li reported that a high amount of H 2 O is suitable for HTL and many organic components in macroalgae are converted to bio-oil . It was considered that the decomposition reaction (HTL) of macroalgae in hot compressed H 2 O was clearly dependent on the H 2 O amount.…”
Section: Resultsmentioning
confidence: 99%
“…Liu and Li reported that a high amount of H 2 O is suitable for HTL and many organic components in macroalgae are converted to bio-oil. 32 It was considered that the decomposition reaction (HTL) of macroalgae in hot compressed H 2 O was clearly dependent on the H 2 O amount. A minute difference of 0.21% was observed for the macroalgae to water ratio of 1:7 and 1:10.…”
Section: ■ Process Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, further investigations are necessary to gain more insights into gas evolutions. pressure, which should be relevant to more hydrophobic characteristic of hydrochars (Liu and Li, 2014). On the other hand, during HTC of sludge, formation of water soluble oil was favored at lower temperatures while increased temperature led to higher water insoluble heavy oil (HO) yield (Xu and Lancaster, 2008).…”
Section: Combustion Of Dssmentioning
confidence: 99%
“…Several processes, such as thermal‐chemical process and biochemical process, can be applied to convert lignin into fuel or chemicals. Hydrothermal liquefaction (HTL), a kind of thermal‐chemical conversion technique, uses liquid subcritical or supercritical water as reaction medium for the conversion of biomass and waste streams . In that process, with high‐temperature and high‐pressure water, organic macromolecules are depolymerized into low‐molecular‐weight compounds and monomers, meanwhile some resultant products are still obtained in different phases, namely, gas phase, solid phase, and liquid phase.…”
Section: Introductionmentioning
confidence: 99%